“GUE LO”: FORM OF ADDRESS AS A STRATEGY FOR NEGOTIATING CULTURAL IDENTITY - Rahmawanto, Dwi (International Review of Humanities Studies, 2025)
This study examines the relationship between language choice, especially the use of the form of address gue lo, and the disclosure of the cultural identity of Javanese students at Universitas Indonesia. This study adopts a descriptive mixed-methods approach, combining quantitative and qualitative data collected through a survey of 52 Javanese student respondents. The results indicate that most respondents used the form of address gue lo when interacting with peers from outside Java, whereas alternative forms were more commonly used with other Javanese students. Correlation tests revealed a negative relationship between the intensity of gue lo usage and the desire to express cultural identity. That is, the higher the desire to show Javanese identity, the less frequently gue lo was used. The findings imply that language choice serves both as an adaptation strategy and a means of asserting identity in multicultural interactions. These findings can be used as a basis for further research to explore the relationship between language as a form of representation and its influence on social dynamics within diverse societies such as Indonesia.